CONDUCTING ENGLISH LEARNING ACTIVITIES BY IMPLEMENTING TELEGRAM GROUP CLASS DURING COVID-19 PANDEMIC - Dian Arsitades Wiranegara; Sohibul Hairi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The use of telegram can be used to hold a meeting just like the regular class conducted. Teacher can still observe all members of the group—students—belong to the class once both parties start to chat or to keep online within the chat in telegram group. Therefore, every meeting within the group, teacher can share his or her teaching material into the group and discuss it along with the students. This also means that the use of social media group such as: whatsapp or telegram group can help learners to experience a different way of conducting teaching and learning process. However, the process may take a while compared to the face-to-face weekly regular class. This distance class, of course, can be a new experience by both teacher and students as it needs further investigation about how this can be conducted accordingly. Nonetheless, during these four meetings conducted individually at home, both teacher and students are still able to catch up all the material given within the social media group. As a result, in order to achieve the effective learning process of English language class during the Covid-19 pandemic, the distance class should not burden the students as long as the learning process can be conducted efficiently. Hence, by using telegram group, teacher and students can keep in touch or communicate intensively in discussing the teaching material. At the end of teaching and learning process, students can later be given a chance to improve their learning strategy to become a long life learner despite any condition experienced by them